Análise ambiental para implantação de distritos industriais com o uso do geoprocessamento no município de São Leopoldo - RS - Baretta, Luciane (Universidade do Vale do Rio dos Sinos, 2007)
Since the 19th century, cities have been passing through a transformation without precedents that is strongly related to the high acceleration of industrialization in great world centers. Since then processes of soil occupation and natural resources exploitation have evidenced a reality that shows no harmony with the concept of sustainable development, making it necessary a revaluation and replacement of the methods practiced in relation to planning the use of soil. Industrial Districts became important instruments which are used by the Public Power to induce economic decentralization and create new development poles. For this reason, the legislative process is an indispensable means to define the priorities in the uses of soil, also to conduct and follow the process of industrial registration. However, the Industrial District establishment shall not be analyzed by taking into account the economic factor only, but also the environmental issue of the enterprise. Thus, this research has the objective of determining adequate places for Industrial District implantation, having as a pilot area the city of São Leopoldo - RS. A Geographic Information System for the execution of spatial analysis and criteria creation on a large volume of environmental information will be used as a tool, which will be studied by Federal, State and Municipal legislation. The main information used on this research are: altimeter, hydrography, soil use, pedology, geology and infrastructure. The results will be visualized in scenarios modeled in accordance with the restrictions imposed upon the information, allowing at the end, to combine all scenarios and create the map that indicates the adequate places for Industrial Districts implantation. For São Leopoldo, around 58.99% of their total area, was considered Permanent Preservation Area (PPA), but 32.46% of these areas are occupied by buildings and reforestations. However, even proposing that more than a half of municipality total area must be preserved, was obtained as final result a considerable proportion of suitable areas for industrial districts implantation, where 31.69% were considered good and best, and 8.84% medium.
Keywords: Análise ambiental; Distrito industrial; Sistema de Informação Geográfica; Environmental analysis; Industrial district; Geographic Information System; ACCNPQ::Ciências Exatas e da Terra::Geologia